Investigation Of Different Harvesting Methods For Microalgae Coccomyxa Sp. Biomass - Khoo, Zenyang (Universiti Sains Malaysia, 2020)
Microalgae harvesting methods can currently be classified as mechanical, chemical, biological and electrical. Centrifugation, flocculation and filtration are among the top three preferred harvesting techniques to obtain microalgal biomass for applications such as biofuel, human and animal food, and water quality restoration. The present study investigated the variables affecting the biomass recovery efficiency via centrifugation, flocculation and filtration method.